2020
DOI: 10.1016/j.clinthera.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress and Chronic Urticaria: A Neuro-immuno-cutaneous Crosstalk. A Systematic Review of the Existing Evidence

Abstract: Purpose: It has been observed that certain patients with chronic spontaneous or idiopathic urticaria (CSU/ CIU) have a personal history of a significant stressor before urticaria onset, while the prevalence of any psychopathology among these patients is significantly higher than in healthy individuals. Research has confirmed that skin is both an immediate stress perceiver and a target of stress responses. These complex interactions between stress, skin, and the nervous system may contribute to the onset of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 73 publications
0
29
0
3
Order By: Relevance
“…In regard to mental health care, an acute public health event can act as a stressor. A stressor refers to a type of environmental stimulus that leads to a specific psychological and physiological response in an individual, which threatens the individual’s important needs and coping ability (Konstantinou & Konstantinou 2020; Li & Hasson 2020). The key characteristics and unknown details of the event itself can increase people’s uncertainty about the causes of the public health event and the means to deal with it; thus, they are prone to experiencing stress manifesting as anxiety, fear, and other emotions (Main et al .…”
Section: Introductionmentioning
confidence: 99%
“…In regard to mental health care, an acute public health event can act as a stressor. A stressor refers to a type of environmental stimulus that leads to a specific psychological and physiological response in an individual, which threatens the individual’s important needs and coping ability (Konstantinou & Konstantinou 2020; Li & Hasson 2020). The key characteristics and unknown details of the event itself can increase people’s uncertainty about the causes of the public health event and the means to deal with it; thus, they are prone to experiencing stress manifesting as anxiety, fear, and other emotions (Main et al .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with spontaneous urticaria, compared to those with inducible urticaria, are shown to have significantly higher urticarial activity and a stronger perception of stress 9 . Also, another study showed a significant association between stress levels, systemic inflammation, elevations (IL) -18, and C-reactive protein (CRP) levels, and this relationship was even more pronounced in patients with a more severe clinical representation and other autoimmune diseases 8 . In addition, several studies have shown that abnormalities in the functioning of the hypothalamic-pituitary-adrenal axis (HPA axis) are present in patients suffering from urticaria 8 .…”
Section: Copyright (C) 2021 Jerković H Bešlić I ćEsić D šItum M This ...mentioning
confidence: 98%
“…Both research studies and clinical experience show that various dermatological diseases are psychosomatic, urticaria being one of them. Research suggests that the relation between stress and urticaria is due to complex interrelations of the neurological and immune systems with the skin, involving numerous neuropeptides, neurokinins, inflammatory mediators, and HPA axis cells and hormones 8 . The results of a recently published systematic review clearly show that many patients experience elevated levels of psychological stress before the onset of urticaria and link the onset and worsening of the disease to unpleasant and stressful experiences 8 .…”
Section: Copyright (C) 2021 Jerković H Bešlić I ćEsić D šItum M This ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Few epidemiologic studies have addressed this question, but a recent review summarized the neuro-immuno-cutaneous crosstalk as a mechanism that links psychological stress and urticaria. 4 The outbreak of COVID-19 uniquely creates a quasi-experiment and provides an opportunity to study this association. We assumed that the income loss could increase urticaria activity through mental stress; hence, we conducted a social media–based investigation in adult Chinese patients between February 27, 2020, and March 11, 2020.…”
mentioning
confidence: 99%